Short Chain Fatty Acid Concentrations in the Cecum of Obese Rats after Giving Dangke (Fermented Milk) from Enrekang - Magfirah, Ariel; Diana Nur Afifah; Endang Sri Lestari; Pramono, Adriyan; Rustanti, Ninik (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Obesity is one of the main causes of metabolic syndrome. This incident is triggered by an imbalance in the intestinal microbiota, resulting in inflammation, impaired tissue function and insulin resistance. Lactic acid bacteria, which are probiotics capable of balancing the gut microbiota, are present in fermented milk. The purpose of this study is to evaluate the variations in SCFA concentrations following dangke administration. The method in this research was a true experimental design, specifically a completely randomized, post test only design with a control group. This study used thirty male Sprague Dawley rats were split up into five equal groups, obesity intervention (X1, X2 and X3), obese control (P1), and health control (P0). A high fat sucrose diet (HFSD) was used to promote obesity in P1, X1, X2 and X3, whereas (P0) served as a healthy control group. Additionally, the X1, X2, and X3 groups received doses of L-Bio at 0,018 g/200 g body weight, dangke at 1,8 g/200 g bodyweight, and dangke at 3,6 g/200 g bodyweight, respectively for 28 days. Data were analyzed statistically with One Way Anova test and significant data (<0.05) were further tested using Bonferroni Post Hoc test.  The result of this study showed the highest SCFA Acetate, Propionat, Butirat, and Total of SCFA (P0> X3> X2> X1, P1) (p=0.000). The conclusion of this study found that giving a dose of 3.6 g/ 200 g body weight of dangke could elevate SCFA levels thereby, dangke can enhance obesity management by boosting the synthesis of SCFA.